Study of probiotic effect on Staphylococcus epidermidis and Staphylococcus haemolyticus isolated from urinary tract catheters (Eurasian Medical Research Periodical, 2023)
Catheter associated urinary tract infection consider one of the most common source of hospital acquired infections. A total of 188 samples, from various urinary tract catheterized patients, a total 116 samples revealed bacterial growth. Most infections of urinary tract catheter were more common in patients of ages above 50 years and whose catheterization period exceeded six days. the affectivity of antimicrobial agent of Lactobacillus spp. Lactobacillus acidophilus (L acidophilus) besides Lactobacillus casie(L casie) was detected by well diffusion method. L casie showed high level of ability to inhibition growth of S epidermidis and S haemolyticus than L acidophilus. Highest inhibition zone is indicated by bacterial cell broth P˂0.05 between 19mm and 20mm for L acidophilus and L casie, respectively, while larger inhibition zone was observed by cell free supernatant (11mm) and (12mm) for Lactobacillus acidophilus and Lactobacillus casie, respectively.